Madagascar rice bowl of COMESA, ten years after? - Razafindrakoto Jean Lucien (World Scientific Reports, 2023)
Talking does not cook rice, Chinese Proverb This paper was written to analyze Madagascar’s ability to increase rice production in order to export rice in general and become the COMESA rice granary in particular. We used a linear model to estimate the relationship between cultivated area, annual production, and market price of rice. National economic data from 2016 to 2020 are used as the basis for the study. The results show that production is more elastic with respect to area cultivated than to price. Other factors, such as changes in the production structure, such as the cropping system and the means of production (equipment, agricultural credit), must therefore be taken into account to increase production.